Penggunaan jamu herbal pada ayam leghorn umur 26 bulan terhadap kualitas protein, lemak dan kolesterol telur - Riana Wijayanti; Nurcholis Nurcholis; Heny V Saiya (Faculty of Agriculture, Musamus University, 2019)
Laying hens raised in Merauke are generally medium-type leghorns with their characteristic brown feathers, two-year-old laying hens have decreased egg production because the chickens have entered the rejected period. Chicken is said to be rejected because the chicken has experienced a molting period twice and also has a period of decreased egg production. Efforts to improve the quality of production as well as eggs from medium type chicken rejects include giving herbal medicine. Improving the quality of production and the quality of eggs can not be separated from the condition of the chicken reproductive organs, herbal plants function to increase the fertility of the reproductive organs because they contain carotene and tocopherol which function to increase the fertility of the reproductive organs of one type of plant such as red fruit (Pandanus conoideus). The purpose of this study was to determine the ability of herbal medicine to improve the quality of egg protein, fat and cholesterol in laying hens. This research method was conducted experimentally using 26-month-old laying hens as many as 36 heads, with normal feeding and drinking provision divided into 4 treatments and 3 replications, so there were 12 units, each unit consisting of 3 chickens. Data were analyzed anovaally and continued with duncan test, calculations using SPSS 21 software. The results showed that the use of herbal herbal medicine in drinking water for fat and cholesterol protein had decreased but was not significant. The conclusion of this research is the supplementation of herbal herbal medicine in laying hens of medium type rejects does not affect the quality of eggs, namely protein, fat and cholesterol. The content of quality protein, fat and cholesterol is still in normal levels.